Rodinný dům v Litovli - Pischl, Jiří (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Předmětem bakalářské práce je novostavba rodinného domu v Litovli, okres Olomouc. Jedná se o dřevostavbu s dvěma podlažími, bez podsklepení, s garáží. Stavba je zastřešena pultovou střechou.

The theme of the bachelor’s thesis is a new building of a detached house in Litovel, district Olomouc. It is a wooden house with two-storeys, without a basement, with a garage. The building is roofed with a aisle roof.
Family residence in Litovel
Keywords: Rodinný dům; dřevostavba; pultová střecha; Detached house; wooden house; garage; aisle roof